remote sensing surface energy balance algorithm for land (SEBAL). 2. Validation - Bastiaanssen, W.G.M; Pelgrum, H; Wang, J; Ma, Y; Moreno, J.F; Roerink, G.J; Wal, T. van der (Journal of hydrology (Amsterdam), 1998)
The surface fluxes obtained with the Surface Energy balance Algorithm for Land (SEBAL), using remote sensing information and limited input data form the field were validated with data available from the large-scale field experiments EFEDA (Spain), HAPEX-Sahel (Niger) and HEIFE (China). In 85% of the cases where field scale surface flux ratios were compared with SEBAL-based surface flux ratios, the differences were within the range of instrumental inaccuracies. Without any calibration procedure, the root mean square error of the evaporative fraction delta (latent heat flux/net available radiation) for footprints of a few hundred metres varied from lambdaRMSE = 0.10 to 0.20. Aggregation of several footprints to a length scale of a few kilometres reduced the overall error to five percent. Fluxes measured by aircraft during EFEDA were used to study the correctness of remote sensed watershed fluxes (1,000,000 ha):The overall difference in evaporative fraction was negligible. For the Sahelian landscape in Niger, observed differences were larger (15%), which could be attributed to the rapid moisture depletion of the coarse textured soils between the moment of image acquisition (18 September 1992) and the moment of in situ flux analysis (17 September 1992). For HEIFE, the average difference in SEBAL estimated and ground verified surface fluxes was 23 W m-2, which, considering that surface fluxes were not used for calibration, is encouraging. SEBAl estimates of evaporation from the subsealevel Qattara Depression in Egypt (2,000,000 ha) were consistent with the numerically predicted discharge from the groundwater system. In Egypt's Nile Delta, the evaporation from a distributed field scale water balance model at a 700,000 ha irrigated agricultural region led to a difference of 5% with daily evaporative fluxes obtained from SEBAL. It is concluded that, for all study areas in arid zones, the errors average out if a larger number of pixels is considered. Part 1 of this chapter deals with the formulation of SEBAL.